2008
DOI: 10.1093/annonc/mdn040
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor (IGF) 1 and 2 help to predict disease outcome in GIST patients

Abstract: The expression of IGF1 and IGF2 seems to predict relapse in GIST patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 37 publications
2
57
0
Order By: Relevance
“…29 Similarly, previous studies have suggested that both adult and pediatric WT GISTs may share alterations in IGF-1 pathway. [30][31][32][33] By merging copy number and gene expression data, we observed a high level of correlation between CNAs and the correspondent gene expression profile. This was especially true on chromosome 14, in the q23.1-qter region, which harbors several possible target genes (DAAM1, RTN1, PPM1A, DACT1, MPP5, SNW1, FOXN3, PPM1A and PTPN21).…”
Section: Discussionmentioning
confidence: 98%
“…29 Similarly, previous studies have suggested that both adult and pediatric WT GISTs may share alterations in IGF-1 pathway. [30][31][32][33] By merging copy number and gene expression data, we observed a high level of correlation between CNAs and the correspondent gene expression profile. This was especially true on chromosome 14, in the q23.1-qter region, which harbors several possible target genes (DAAM1, RTN1, PPM1A, DACT1, MPP5, SNW1, FOXN3, PPM1A and PTPN21).…”
Section: Discussionmentioning
confidence: 98%
“…It is therefore interesting to find downregulated IGF1 expression in SKP2-silenced myxofibrosarcoma cells. Actually, the ligand binding of IGF1 to IGF1 receptor has been shown to activate signaling cascades in several soft tissue sarcomas, thereby contributing to their tumorigenesis (35,36). Notably, SKP2 knockdown also negatively regulated expression of ENAH gene encoding the hMENA protein, a member of enabled (Ena)/vasodilator-stimulated phosphoprotein (VASP) family.…”
Section: Discussionmentioning
confidence: 99%
“…Expression arrays and Western blots have identified adult sarcomas subtypes that have the greatest relative amount of IGFs at the mRNA or protein level. [114][115][116][117][118][119][120] For example, as a surrogate for IGF1R signaling, those sarcomas with highest IGF2 expression by immunohistochemistry include SFT/HPC, malignant peripheral-nerve sheath tumor, GIST, and synovial sarcoma (Fig 2). 120 Although consistent expression would not foreordain a good response to agents that block the target, subtypes can be eliminated for testing that lack expression of the target of interest, understanding that our screening tests may be insensitive for assessing expression of a relevant protein.…”
Section: Igf1r and Sarcomas More Commonly Observed In Adultsmentioning
confidence: 99%